A simple, rapid method for the extraction of whole fire ant venom (Insecta: Formicidae: Solenopsis) - Gonçalves Paterson Fox, Eduardo; Russ Solis, Daniel [UNESP]; Delazari dos Santos, Lucilene [UNESP]; Aparecido dos Santos Pinto, Jose Roberto [UNESP]; Ribeiro da Silva Menegasso, Anally [UNESP]; Cardoso Maciel Costa Silva, Rafael; Palma, Mario Sergio [UNESP]; Correa Bueno, Odair [UNESP]; de Alcântara Machado, Ednildo (Elsevier, 2013)
The invasive fire ant Solenopsis invicta is medically important because its venom is highly potent. However, almost nothing is known about fire ant venom proteins because obtaining even milligram-amounts of these proteins has been prohibitively challenging. We present a simple and fast method of obtaining whole venom compounds from large quantities of fire ants. For this, we separate the ants are from the nest soil, immerse them in dual-phase mixture of apolar organic solvent and water, and evaporate each solvent phase in separate. The remaining extract from the aqueous phase is largely made up of ant venom proteins. We confirmed this by using 2D gel electrophoresis while also demonstrating that our new approach yields the same proteins obtained by other authors using less efficient traditional methods. © 2013 Elsevier Ltd.
Keywords: Allergen; Chromatography; Hymenoptera; Myrmecology; Toxin; alkaloid; ant venom; hexane; hydrocarbon; aqueous solution; evaporation; extraction; lyophilisate; mass spectrometry; nonhuman; phase separation; precipitation; priority journal; protein analysis; separation technique; Solenopsis; storage temperature; two dimensional gel electrophoresis; Animals; Ant Venoms; Ants; Chemical Fractionation; Electrophoresis, Gel, Two-Dimensional